Pharmacovigilance: an evaluation on the practice of pharmacists acting in pharmacies and drugstores - Mayra Bruna Fedalto; Fernanda Stumpf Tonin; Helena Hiemisch Lobo Borba; Vinicius Lins Ferreira; Cassyano Januário Correr; Fernando Fernandez-Llimos; Roberto Pontarolo (Universidade de São Paulo, 2022)
Abstract Pharmacists acting in pharmacies and drugstores stores are some of the most accessible healthcare providers and the last to intervene before the patient takes their medicine. This puts the pharmacist in a position of authority that should be harnessed for the benefit of health. Thus, this professional is strategic for performing pharmacovigilance. Our objective of this study was to interrogate the practice of pharmacists in relation to pharmacovigilance activities, and to identify difficulties and possible stimuli for the improvement these activities in pharmacies and drugstores. The information was collected through an online questionnaire via Survey Monkey®. The data were analyzed statistically using SPSS software. Responses were received from 5174 pharmacists: mostly young women within five years of graduation and experience in pharmaceutical retail. 81% of them reported having identified suspected substandard medicines, but only 16% used the Brazilian notification system Notivisa. More than 85% of pharmacists agreed with the importance of pharmacovigilance and the recognition of reporting services as part of pharmacist duties and pharmaceutical care. The main barriers to making notifications were the lack of access and knowledge about Notivisa. Pharmacists agreed that simplifying the system would be a stimulus for notifications, and requested more feedback from notifications, as well as material and courses to understand the notification process. Pharmacists have important data to feed into pharmacovigilance systems, recognize their responsibilities and are willing to contribute, but still demonstrate low compliance. Simplification of the system and training on it are likely to increase notifications.